Pengaruh Kualitas Pelayanan terhadap Loyalitas Pelanggan PDAM Kota Surakarta dengan Kepuasan Pelanggan sebagai Variabel Intervening - krisna, teofilus wahyu (Universitas Slamet Riyadi, 2020)
This study aims to determine the significance of service quality that is thought to have an influence on customer loyalty in the city of Surakarta with customer satisfaction as an intervening variable. Sampling was taken with non probability sampling by purposive sampling. Data collection techniques using a questionnaire through the test of validity and reliability. The analysis technique is through descriptive analysis and path analysis, t test, F test, R2 test and classic assumption test. From the results of the validity test, the research instrument is valid. The reliability test results are reliable. From the classic assumption test, the multicollinearity test passed the test, the heteroscedasticity test passed the test, the autocorrelation test passed the test and the normality test passed the test. The results of the analysis show that, service quality and customer satisfaction have a significant effect on customer loyalty